On propagation rules for entanglement-assisted quantum codes - Luo, Gaojun (2024)
This paper proposes new propagation rules on quantum codes in the entanglement-assisted scenario. The rules lead to new families of such quantum codes whose parameters are demonstrably optimal. To obtain the results, we devise tools to puncture and shorten codes in ways that ensure their Hermitian hulls have certain desirable properties.